Questioning risk compensation: pre-exposure prophylaxis (PrEP) and sexually transmitted infections among men who have sex with men, capital region of Denmark, 2019 to 2022 - von Schreeb, Sebastian; Pedersen, Susanne Kriegel; Christensen, Hanne; Jørgsensen, Kristina Melbardis; Harritshøj, Lene Holm; Hertz, Frederik Boetius; Ahlström, Magnus Glindvad; Lebech, Anne-Mette; Lunding, Suzanne; Nielsen, Lars Nørregaard; Gerstoft, Jan; Kronborg, Gitte; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2024)
BackgroundPre-exposure prophylaxis (PrEP) effectively prevents HIV, but its association with sexually transmitted infections (STIs) has raised concerns about risk compensation, potentially impacting the expansion of PrEP programmes.AimWe examined the relationship between PrEP and the incidence of chlamydia, gonorrhoea and syphilis.MethodsIn this prospective cohort study, we compared STI rates before and after PrEP initiation among users in the capital region of Denmark (2019-2022), calculating incidence rate ratios adjusted for age and testing frequency (aIRR). To pinpoint when increases began, we plotted weekly STI rates, adjusting the timeline to correspond with PrEP initiation.ResultsThe study included 1,326 PrEP users with a median age of 35 years. The STI incidence rate per 100,000 person-years rose from 35.3 before to 81.2 after PrEP start, with an aIRR of 1.35 (95% CI: 1.18-1.56). Notably, this increase preceded PrEP initiation by 10-20 weeks. Specific aIRR for chlamydia, gonorrhoea and syphilis were 1.23 (95% CI: 1.03-1.48), 1.24 (95% CI: 1.04-1.47) and 1.15 (95% CI: 0.76-1.72), respectively. In subanalyses for anatomical sites aIRR was 1.26 (95% CI: 1.01-1.56) for rectal chlamydia and 0.66 (95% CI: 0.45-0.96) for genital gonorrhoea.ConclusionWe found a 35% increase in STI incidence associated with PrEP use. It started before PrEP initiation, challenging the assumption that PrEP leads to risk compensation. Instead, the data suggest that individuals seek PrEP during periods of heightened sexual risk-taking. Consequently, PrEP programmes should include sexual health consultations, STI testing, treatment and prevention strategies to prevent HIV and improve sexual health.